Respuesta :

10 x 7 = 70
1 x 7 = 7
9 x 7 = 70 - 7
9 x 7 = 63

Thomas' strategy is to write the given expression in a different form, also known as the equivalent form.

The expression is given as:

[tex]\mathbf{9 \times 7}[/tex]

Express 9 as 10 - 1

[tex]\mathbf{9 \times 7 = (10 - 1) \times 7}[/tex]

Distribute the expression. i.e. open the bracket

[tex]\mathbf{9 \times 7 = 70 - 7}[/tex]

Solve the expression on the right-hand side of the equation

[tex]\mathbf{9 \times 7 = 63}[/tex]

Recall that [tex]\mathbf{9 \times 7 = 70 - 7}[/tex].

So, we have:

[tex]\mathbf{70 - 7 = 63}[/tex]

Hence, both expressions are equivalent expressions

Read more about equivalent expressions at:

https://brainly.com/question/4348710

ACCESS MORE